Medical students’ preference of problem-based learning or traditional lectures in King Abdulaziz University, Jeddah, Saudi Arabia - Ibrahim, Nahla Khamis (Ann Saudi Med, 2014)
BACKGROUND AND OBJECTIVES: Problem-based learning (PBL) is the most important educational innovations in the past 4 decades. The objective of the study was to compare between the preference of medical students for PBL and the preference for traditional lectures regarding learning outcomes (e.g., knowledge, attitude, and skills) gained from both methods. DESIGN AND SETTINGS: A cross-sectional study was conducted among medical students who studied the hybrid curriculum (PBL and traditional lectures) in King Abdulaziz University, Jeddah, in 2011. METHODS: Data was collected through a pre-constructed, validated, confidentially anonymous, and self-administered questionnaire. Students’ perceptions toward PBL and traditional lectures were assessed through their response to 20 statements inquired about both methods of learning using a five-point Likert scale. Descriptive and analytic statistics were performed using SPSS, version 21 (SPSS Inc, Chicago, Ill., USA). RESULTS: Learners preferred PBL more to traditional lectures for better linking the knowledge of basic and clinical sciences (t test=10.15, P<.001). However, no statistical significant difference (P>.05) was observed regarding the amount of basic knowledge recalled from both methods. Students preferred PBL more to lectures for better learning attitudes, skills, future outcomes, and learning satisfaction (P<.05). PBL motivates students to learn better than lecturing (P<.05). From students’ opinion, the mean total skill gained from PBL (47.2 [10.6]) was much higher than that of lectures (33.0 [9.9]), and a highly statistical significant difference was observed (t test=20.9, P<.001). CONCLUSION: Students preferred PBL more to traditional lectures for improving most of learning outcome domains, especially, learning attitudes and skills. Introducing hybrid–PBL curriculum in all Saudi universities is highly recommended.